Semantic features of syntactic constructions. (Journal of Oriental Studies, 2016)
In this paper a more detailed explanation of the semantic features of the turk words that describe turk way of thinking.
Keywords: Mahmud Kashgari; Divan Lugat at-Turk; semantics